PERLAWANAN AL-QURAN DAN HADIS TERHADAP KEMISKINAN - M. Ali Musyafak (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2017)
There is no doubt, that poverty is great danger of the religious beliefs, Especially extreme poverty severe, who were in front of the eyes of rich egoistic people. More worried, if poor people do not have jobs,and rich people do not want to give their hand. That is when the poverty will invite doubt against sunnatullah (provisions god) above this world. And cangive confidence in the injustice in a division of fortune. That is the dangerous of declining of aqeedah that is caused by poverty. As the word of Rasulullah, “almost poverty make people become atheist.”Sayyidina Ali ra said that if the poverty like a men, I will kill them. Al Quran and Hadis give guidance to against poverty, the guidance has two aspects. The guidance from individual as hard work and simple living, and the guidance from social as management zakat productive, charity productive and infaq.